Infecção de sítio cirúrgico em pacientes submetidos a procedimentos ortopédicos com implante, em um hospital público de Belo Horizonte, Minas Gerais - Lucia Maciel de Castro Franco (2013)
Surgical site infection (SSI), resulting from the surgery with the use of implant, is considered a severe event causing injury to the patient, health institution, family and society. The systematic surveillance of these patients in the postoperative period it becomes essential for the recognition of reliably risk factors that cause the SSI and guide prevention and control measures. The method of surveillance by telephone has been identified as a practice with good return rate. This study was prospective cohort of 222 patients undergoing orthopaedic surgery with implantation, in the period May to September 2011, with follow-up post-hospital discharge, during a year, by telephone contact. Its general objective was to evaluate the epidemiologic aspects The SSI in patients undergoing orthopedic surgery with implants, a public hospital in Minas Gerais. Specific objectives were to characterize the study population; estimate the incidence of SSI global, by procedures and by topographies; identify, among the collected variables, which are risk factors for the SSI; estimate the time of the manifestation of SSI; identify the type of implant used in orthopedic surgery and its nature; identify the etiologic agents responsible for SSI and resistance profile of these microorganisms; estimate the rate of mortality, the number of events not infectious and the functional disability of patients daily activities one year after surgery. We used methodology NHSNCDC. For the descriptive analysis was used to simple frequency and measures of central tendency as mean, median and of variability as standard deviation.To check the association between the risk factors and the occurrence of SSI was held in the survival analysis using Kaplan Meier in the univariate analysis and Cox regression for the multivariate analysis. The population was characterized by female patients, the elderly (>60 years) and above the body weight (BMI >25 kgm2). Were notified 28 ISC with overall rate of 12.6% and 20 SSI (71.4%) occurred among patients in orthopedic trauma. On the topographies surface infections were more incidents (6.7%) for procedures the reduction of open long bone (14.1%). The average time to acquire an infection was 39.7 days. The Staphylococcus aureus was etiologic agent more isolated. Were diagnosed 119 adverse events infectious and non-infectious after a year of monitoring of these, 28 (23.5%) were related to the functional disability of the patient to activities daily living. The mortality rate was 4.5 %, and in patients with femoral fracture 10.4 %. The implants were more used plates and screws in 98 (44.1%) procedures and imported implants were used in 125 (56.3%) procedures. The result of the final adjustment of the Cox model defined as risk factors for infection in orthopedic surgery with implantation: male gender, do not perform blood glucose on surgical risk, the previous surgery in operated site, do not take the bath before surgery, blood transfusion, be the bearer of renal disease and does not comply with the protocol of pelvic antisepsis of hands. Concluding the rates of SSI was above the recommended in the NHSN.